Identification of Threats To The Sustainability of Smallholder Dairy Farming Using A Multidimensional Risk Perspective - Erma Malika, Uyun; Ahmad Hudori, Huda; Perlambang CNAWP, Rizal; Prasetyo, Budi (Publisher Cv. Inara, 2025)
The sustainability of dairy cattle businesses in smallholder farms faces various complex and interconnected threats, especially after the outbreak of Foot-and-Mouth Disease, which worsened the national cattle population and milk production. This research aims to identify threats to the sustainability of dairy cattle businesses in Suci Village, Panti District, Jember, using a multidimensional risk approach that includes ecological, economic, social, technological, and institutional dimensions. A quantitative approach was used with a census method on 25 dairy farmers as respondents, using a structured questionnaire. The research results indicate that the majority of dairy farms fall into the